Physician awareness and understanding of hereditary angioedema: A web‐based study in Japan. Issue 5 (29th June 2022) - Fukunaga, Atsushi; Kishimoto, Miwa; Oh, Akinori; Akiyama, Takeshi; Kotera, Ippei; Inoue, Yoichi; Maehara, Junichi
Abstract: Objectives: Hereditary angioedema (HAE) is a rare disease with acute attacks in the skin and mucosa throughout the body including life‐threatening laryngeal edema and abdominal attacks with severe pain. Physicians, regardless of specialty, may encounter HAE patients in their daily practice; however, low disease awareness may attribute to a considerable number of undiagnosed HAE patients in Japan. This study aims to identify issues associated with the diagnosis processes of HAE and to determine levels of HAE awareness among Japanese physicians from various specialties. Methods: A web‐based quantitative survey was conducted using a physicians panel. Physicians from the following departments were included in the survey: internal medicine, dermatology, pediatrics, emergency medicine, and gastroenterological surgery. Results: The proportions of physicians in dermatology, pediatrics, emergency medicine, internal medicine, and gastroenterological surgery who were able to select the C1‐INH activity test as a diagnosis test for potential HAE patients were 71.8%, 59.7%, 57.1%, 40.3%, and 25.7%, respectively. Multivariate analysis showed significant association between physicians who selected "strongly suspected" AE based on the case‐scenario and physicians who had knowledge of the essential HAE symptoms (laryngeal edema, swelling after tooth extraction, swelling of the tongue, and abdominal pain). Conclusions: This study showed that disease awareness of HAE varied among medical specialties, suggesting the importance of educational activities in academic societies and specialist accreditation in raising HAE awareness. Proper knowledge of complement testing and HAE symptoms may help not only to diagnose patients with AE‐like symptoms as AE but also to differentially diagnose HAE from AE. Abstract : We conducted a questionnaire survey among physicians of different specialties in Japan to evaluate the knowledge of hereditary angioedema (HAE), a rare disease sometimes entailing critical symptoms. The study demonstrated the thinking process for the diagnosis of angioedema that differs among physicians, and the key factors that lead to the diagnosis of hereditary angioedema. Proper knowledge of complement testing and symptoms of HAE may help not only to diagnose patients with AE‐like symptoms as AEs, but also to differentially diagnose HAE from AEs.